Rcf1 Modulates Cytochrome c Oxidase Activity Especially Under Energy-Demanding Conditions - Dawitz, Hannah; Schäfer, Jacob; Schaart, Judith M.; Magits, Wout; Brzezinski, Peter; Ott, Martin (Frontiers in Physiology, 2020)
The mitochondrial respiratory chain is assembled into supercomplexes. Previously, two respiratory supercomplex-associated proteins, Rcf1 and Rcf2, were identified in Saccharomyces cerevisiae, which were initially suggested to mediate supercomplex formation. Recent evidence suggests that these factors instead are involved in cytochrome c oxidase biogenesis. We demonstrate here that Rcf1 mediates proper function of cytochrome c oxidase, while binding of Rcf2 results in a decrease of cytochrome c oxidase activity. Chemical crosslink experiments demonstrate that the conserved Hig-domain as well as the fungi specific C-terminus of Rcf1 are involved in molecular interactions with the cytochrome c oxidase subunit Cox3. We propose that Rcf1 modulates cytochrome c oxidase activity by direct binding to the oxidase to trigger changes in subunit Cox1, which harbors the catalytic site. Additionally, Rcf1 interaction with cytochrome c oxidase in the supercomplexes increases under respiratory conditions. These observations indicate that Rcf1could enable the tuning of the respiratory chain depending on metabolic needs or repair damages at the catalytic site.